Analysis of the Effect of Work Shift and Fatigue on Unsafe Action Cause of Workplace Accidents in Technical Workers of PT. X - A. Ferina Herbourina Bonita; Adinda Maharani Jamil Latief; Rifdah Wardani; A. Suci Setiani Annisa; Yusniar Anggraeny (Sean Institute, 2025)
An uncontrolled or unplanned event caused by human, situational, or environmental factors that disrupts the work process with or without resulting in injury, illness, death, or damage to work property. This study aims to determine the effect of work shifts and work fatigue on work accidents with unsafe actions as an intervening variable in engineering workers at PT. X. This study is an analytical observational study using a cross-sectional research design. The population in this study is the total number of engineering workers. The sample in this study amounted to 65 workers determined using the total sampling method where all members of the population were used as samples. The collected data were analyzed using the chi-squared test for bivariate and path analysis for multivariate. The results of the path analysis showed that the work shift variable was not affected by work accidents (p = 0.333), work fatigue had an effect on work accidents (p = 0.029), work shift had an effect on unsafe action (p = 0.002), there was an effect of work fatigue on unsafe action (p = 0.000), there was an effect of unsafe action on work accidents (p = 0.000). Based on the intervening test of work shifts on work accidents with unsafe action, significant results were obtained (p = 0.011) and work fatigue on work accidents with unsafe action obtained significant results (p = 0.006). It can be concluded that the unsafe action variable is an intervening variable in the influence of work shifts, work fatigue, on work accidents. It is hoped that future researchers will expand the population and number of samples to obtain better research results.